Expression of non-phosphorylatable S5A-L-plastin exerts phenotypes distinct from L-plastin deficiency during podosome formation and phagocytosis - Lin, Xue; Krishnamoorthy, Praveen; Walker, Emma C.; Joshi, Hemant; Morley, Sharon Celeste (Frontiers in Cell and Developmental Biology, 2023)
The actin cytoskeleton remodels to enable diverse processes essential to immunity, such as cell adhesion, migration and phagocytosis. A panoply of actin-binding proteins regulate these rapid rearrangements to induce actin-based shape changes and to generate force. L-plastin (LPL) is a 66-kDa, leukocyte-specific, actin-bundling protein that is regulated in part by phosphorylation of the Ser-5 residue. LPL deficiency in macrophages impairs motility, but not phagocytosis; we recently found that expression of LPL in which the S5 residue is converted to a non-phosphorylatable alanine (S5A-LPL) resulted in diminished phagocytosis, but unimpaired motility. To provide mechanistic insight into these findings, we now compare the formation of podosomes (an adhesive structure) and phagosomes in alveolar macrophages derived from wild-type (WT), LPL-deficient, or S5A-LPL mice. Using super-resolution confocal microscopy, we systematically analyzed recruitment of the integrin-binding protein vinculin and the integrin-associated kinase Pyk2 to sites of adhesion or phagocytosis. As described previously, podosome structure and stability were significantly disrupted by LPL deficiency, with displacement of Pyk2 from podosomes. In contrast, podosome structure was largely intact in the presence of S5A-LPL, although long-term stability and Pyk2 retention was diminished. LPL was not required for phagocytosis and was not significantly recruited to sites of pneumococcal engulfment. In the absence of LPL, recruitment of vinculin to sites of phagocytosis was significantly enhanced. Expression of S5A-LPL impeded phagocytosis and reduced the recruitment of vinculin and Pyk2 to phagosomes. We propose a model reconciling these findings, in which LPL is recruited to podosomes independently of phosphorylation, while longer term maintenance of the podosome structure and Pyk2 retention requires Ser-5 phosphorylation. Meanwhile, phagosomes do not include LPL; further, Ser-5 phosphorylation of LPL regulates the association of vinculin with some actin structures, and when LPL cannot be phosphorylated at Ser-5, vinculin is sequestered and therefore inefficiently recruited to phagosomes, impairing phagocytosis. Our systematic analysis of the regulation of LPL during podosome vs phagosome formation illuminates essential remodeling of actin during key immune processes.